Anatomy and physiology of leaf coffee plants in different fertilizing levels - da Gama, Tamara Cubiaki Pires; Sales Junior, José Carlos; Castanheira, Dalyse Toledo; Silveira, Helbert Rezende de Oliveira; de Azevedo, Harianna Paula Alves (Coffee Science - ISSN 1984-3909, 2017)
The mineral nutrition is important for the development of the internal structure of coffee leaves, which may favor the physiological characteristics required to optimize the development and productivity of the culture. This study aimed to identify possible changes in anatomy, physiology and productivity in coffee plants at different fertilization levels applied in three consecutive years, from the second year after the implementation of the crop. The Coffea arabica crop cultivar Topazio MG-1190 was formed following the standard recommendation by Guimarães et al. (1999) for fertilization on soil analysis function until the first year after implantation (2010-2011). Thereafter, in the second year after implantation (2011-2012), fertilization levels were: 40, 70, 100, 130 and 160% of the standard fertilization. Treatments were repeated in the years 2012-2013 and 2013-2014. The plants were evaluated for gas exchange and leaf anatomy in August 2014. It was also evaluated the productivity of the years 2013 and 2014. The different NPK levels caused differences in coffee leaf anatomy. Productivity and gas exchanges in the coffee trade were not affected by different levels of NPK fertilization.